Farm trajectories, sustainable intensification and livelihoods in Southern Bangladesh - Jahanara, Ishrat; Zepeda, Adair; Mponela, Powell; Kamal, Mustafa; Aravindakshan, Sreejith; Krupnik, Timothy Joseph; Lopez-Ridaura, Santiago (CIMMYT, 2025)
Report of a farm trajectory study in southern coastal Bangladesh, comparing farm characteristics of two periods (2015/2023). Differences were analyzed through multilevel Principal Components Analysis to identify trajectory types.